Pengaruh Investasi, Tenaga Kerja dan Tingkat Pendidikan terhadap Produk Domestik Regional Bruto di Kalimantan Tahun 2013 s.d. 2020 - Mustikatama, Fitrah Lintang; Wardhana, Ali (PPJP Universitas Lambung Mangkurat, 2023)
Research shows the effect of investment, labor, and education level on gross regional domestic product in Kalimantan. The data used in this study are quantitative secondary data obtained from the Central Statistics Agency and the One Stop Integrated Investment Service from 2014 to 2020. The data in question are investment realization data, the the number of people working in the workforce, the average length of schools, and gross regional domestic product at constant prices. This study uses the Ordinary Least Square method using panel data from 5 provinces in Kalimantan from 2014 to 2020 by testing classical assumptions and hypotheses. Partially, investment and education level have an insignificant positive effect on gross regional domestic product, while labor has a significant positive impact on gross regional domestic product in Kalimantan. Simultaneously, the three independent variables significantly affect the gross regional domestic product. The most influential variable on gross regional domestic product is labor.